PENGARUH BRAND IMAGE DAN BRAND AWARANESS TERHADAP KEPUTUSAN PEMBELIAN PADA ORIESTOM BAY CAFE & RESTAURANT - Bajari, Makarius; Lomo, Angely; Lotte, Luckhy (Lensa Ekonomi, 2025)
This study aims to analyze the influence of brand image and brand awareness on purchasing decisions at Oriestom Bay Cafe & Restaurant in Manokwari. The background of this study is based on the rapid growth of the culinary industry in Indonesia which creates tight competition, so that business actors are required to implement effective marketing strategies. This study was conducted at Oriestom Bay Cafe & Restaurant, in Manokwari. The research method used is an associative quantitative approach with a sample of 90 respondents, taken using a purposive sampling technique. Data were collected through questionnaires distributed to consumers who had made repeat purchases more than twice a month. Data analysis used multiple linear regression to see the relationship between the independent variables (brand image and brand awareness) and the dependent variable (purchase decisions). The results showed that brand image and brand awareness had a positive and significant influence on purchasing decisions at Oriestom Bay Cafe & Restaurant. This shows that an effective marketing strategy through brand image and brand awareness can improve consumer purchasing decisions. This study is expected to be a reference for Oriestom Bay Cafe & Restaurant to improve its sales strategy.